Suicidal Ideation and Suicidal Attempts among the Patients Attending Outpatient Department at Provincial Hospital, Bagmati - Bajracharya, Anu; Kharel, Sagun; Paudyal, Laxmi; Shakya, Sangkin (Nepal Journal of Health Sciences, 2025)
Introduction: Suicide is a critical public health issue with devastating impacts on individuals, families and communities. The consequences are often long-lasting for those left behind.Objective: To assess the suicidal ideation and suicide attempts and its associated factors among the patient attending the Psychiatric Outpatient Department at Provincial Hospital of Bagmati Province.Methods: A Hospital based descriptive cross-sectional research design was carried out among the 246 participants, aged 18 years and above from Psychiatric Outpatient Department of Madan Bhandari Academy of Health Sciences, Hetauda Hospital. Data was collected through structured interview schedule consisting of demographic, personal and family history of suicide and disability, public health questionnaire, Generalized Anxiety Disorder, Alcohol use identification questionnaire test. Data analysis was done by suing SPSS version 16. Descriptive findings were presented in table including frequency, percentage, mean and standard deviation.Result: The mean age of the respondent was 37.5±15.014 years. Proportion of males (64.6%) was greater than female (42.7%). Among the total participants, 40.2% had suicidal ideation, 18.3% of the participants having a planned for suicide and 17.5% attempted suicide. Poisoning (48.3%) is the common method used for suicide by attempters. Family structure, family history of suicide, anxiety, depression was associated factors of suicidal ideation and suicidal attempt.Conclusion: Suicidal ideation, planned and attempted were high among the patient attending in Psychiatric Outpatient Department. The common method used for suicide were poisoning, overdoes of medicine and self-hanging.